2011
DOI: 10.1007/s12524-011-0126-y
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing Study of Sittampundi Anorthosite Complex, India

Abstract: In the present study, The Landsat 7 ETM satellite data was collected for the Sittampundi anorthosites complex and digital image analysis was carried out. The anorthositic rocks available at Sittampundi complex is considered as an equivalent of lunar highland rocks. Hence, a remote sensing study comprises of image analysis and spectral profile analysis was carried out. The satellite data was digitally processed and generated various outputs like band combinations, color composites, stretched outputs, and PCA. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…• Sittampundi rock : This sample is taken from the anorthositic rocks available at Sittampundi (near Salem, Tamil Nadu), India, which are considered close to lunar highland rocks in composition. The plagioclase in these rock samples exhibit an anorthite content in the range An 80−100 (Anbazhagan et al, 2012) in comparison to that in Apollo returned samples which has an anorthite content of ≈ An 95 on average. Pure calcic-anorthite and labradorite are the dominant minerals in this sample.…”
Section: Sample Detailsmentioning
confidence: 76%
See 2 more Smart Citations
“…• Sittampundi rock : This sample is taken from the anorthositic rocks available at Sittampundi (near Salem, Tamil Nadu), India, which are considered close to lunar highland rocks in composition. The plagioclase in these rock samples exhibit an anorthite content in the range An 80−100 (Anbazhagan et al, 2012) in comparison to that in Apollo returned samples which has an anorthite content of ≈ An 95 on average. Pure calcic-anorthite and labradorite are the dominant minerals in this sample.…”
Section: Sample Detailsmentioning
confidence: 76%
“…They are pulverized to a grain size of about 100 µm or smaller. Detailed studies on the rocks of this site are reported by (Anbazhagan et al, 2012;Aarthy et al, 2009).…”
Section: Sample Detailsmentioning
confidence: 96%
See 1 more Smart Citation
“…Principal Component Analysis (PCA) is an image enhancement technique used to utilize the maximum spectral contrast of all bands of multispectral data, and it is more reliable than the original image (Anbazhagan et al 2012, Arivazhagan & Anbazhagan 2017. In another sense, PCA is a statistical analysis approach used to reduce irradiance in the bands, so each band can represent particular features, and a combination of this can be interpreted as more valuable information (Ge et al 2018).…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%
“…The Sittampundi Anorthositic Complex is one of the geological interested provinces, since it is bearing chromite (Ghosh and Konar, 2011) and also considered as occurrence of Platinum Group Elements (PGE) (Balaram, 2006). Beyond this, the mineralogy and the relative percentage of major oxides of Sittampundi anorthsoite is considered as an equivalent of lunar highland anorthositic rock (Anbazhagan and Arivazhagan 2010; Anbazhagan et al, 2012). Hence, the development of a suitable methodology to map and discriminate the different lithology in the anorthosite region, could be applicable to the remote sensing study of lunar surface.…”
Section: Introductionmentioning
confidence: 99%